Evaluation and acceptability of crackers made from a blend of fonio (Digitaria exilis), and conophor nuts (Tetracarpidium conophorum) flours for diabetes mellitus patients - Akeredolu, Ifeoma; Seriki-Mosadolorun, Jummai; Olatidoye, Olawale; Ayegbusi, Temitope B.; Bello, Aishat; Mebude, Igbayilola; Ezedinachi, Chioma (World Nutrition, 2025)
Diabetes mellitus (DM) is a complex disease recognised as one of the leading causes of death and disability worldwide. Diet modification and enhanced food behaviour is necessary for the disease management and the patients’ wellbeing. Disease progression in diabetes is greatly influenced by foods consumption pattern which makes it worrisome for sufferers to snack between meals due to fear of possible rise in blood glucose levels. The study therefore produced crackers (snack) made from fonio and conophor nuts. The ingredients were combined using three (3) ratios of 95: 5%, 90:10%, 85:15%. The proximate composition was analysed as described by association of official analytical chemist (AOAC, 2015) and sensory evaluation was carried out using the 9-point hedonic scale. The population of the study was twenty students. A 9-point hedonic scale was the instrument used for data collection. Mean, standard deviation and Analysis of variance (ANOVA) were used for data analysis. The nutrient composition of analysis showed that the different samples of crackers had appreciable values of protein, fats, and carbohydrate. The sensory evaluation result indicated a significant difference in the mean responses of the students on the sensory evaluation of the cracker samples. However, the control sample followed by Sample B had the highest value for colour, taste, crunchiness, texture and general acceptability. The study concluded that the sample B with 90:10 Fonio and Conophor nut flour is nutritionally and organoleptically acceptable and the consumption should be encouraged among diabetes patients.Keywords: Food behaviour, type-2 diabetes, crack we s, Fonio